Super heat sink/spreader for electronic packaging application - Rahul Promprasit Seet; Afiff, M. Mokthar; Mohd Arif Anuar, Mohd salleh; Flora, Somidin (Ministry of Education, Thailand, 2013)
Rahul Promprasit Seet and his team received Taiwan Special at the 8th International Exhibition for Young Inventors (IEYI 2012), 28th - 30th June 2012 held at Bangkok International Trade and Exhibition Centre (BITEC), Bangkok, Thailand.